Learning disabilities : from identification to intervention - 4 0 16; (Jack McFarlin) Fletcher, Jack M.;Lyon, G. Reid.;Fuchs, Lynn S.;Barnes, Marcia A.; 5 (New York : The Guilford Press, 2007)
An exploration of learning disabilities that covers the history of special education; classification, definitions, identification, and assessment of disabilities; and specific problems in reading, writing, and mathematics.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Research.;Research. -- Learning disabilities.;Learning disabilities;Learning disabilities.;Learning disabilities; 20; 2